The status of the Buddhists of Buryatia in the context of the religious policy of the USSR in the second half of the 1960s — first half of the 1980s - Dashkovskiy P.K.; Traudt E.A. (Вестник археологии, антропологии и этнографии)
Based on the analysis of archival materials from the State Archive of the Russian Federation (Moscow) and the State Archive of the Republic of Buryatia (Ulan-Ude), this article examines the status of the Buddhist community of the Buryat ASSR in the context of the religious policy of the Soviet Union. A particular attention is given to the study of the financial, economic and ritual activities of the Ivolginsky Datsan. It has been determined that the main rites during this period were funeral services, for which the Ivolginsky Datsan receives significant financial resources. The analysis of the dynamics of the staff numbers of the datsan has shown that there was a personnel shortage associated with the advanced age of the lamas, which they tried to solve by various methods. Despite the atheistic policy pursued in the USSR, and all the associated challenges, the religious association of Buddhists continued to develop, which was due to a combination of many factors. One of the important aspects that had a positive effect on the development of Buddhism in Buryatia during this period was the foreign policy of the USSR, during which the Buddhist leaders of the Soviet Union acted as a certain instrument for the implementation of diplomacy with the countries of Southeast Asia.